Favorable immune signature in CLL patients, defined by antigen-specific T-cell responses, might prevent second skin cancers. Issue 8 (3rd August 2018) - Walz, Juliane Sarah; Kowalewski, Daniel Johannes; Backert, Linus; Nelde, Annika; Kohlbacher, Oliver; Weide, Benjamin; Kanz, Lothar; Salih, Helmut Rainer; Rammensee, Hans-Georg; Stevanović, Stefan
Abstract: The course of chronic lymphocytic leukemia (CLL), inducing an immunosuppressed state that also affects T cells as central components of adaptive immunity, predisposes patients to develop second malignancies with skin cancer being the most common. Recently, we found that prevalence of memory T cells with specificity for CLL-associated antigens defined by mass spectrometry-based immunopeptidome analysis correlated with a significant survival benefit. Here, we analyzed our CLL patient cohort for second skin (pre)malignancies and found a significantly lower incidence of skin cancer in the patients showing immune responses to CLL-associated antigens. Surprisingly, CLL-associated antigen-specific immune responses did not associate with clinical characteristics including leukocyte, neutrophil, and thrombocyte count, hemoglobin, immunoglobulin levels, or CD8 + and CD4 + T-cell immune status. Our data indicate that the CLL-specific immune signature of a given patient, defined by antigen-specific T-cell responses, might represent an independent marker to identify CLL patients susceptible for the development of skin malignancies.